A wavelength monitor based on electroabsorption in quantum well waveguide photodiodes - Wu, xiucheng (My University, 1999)
A wavelength monitor, based on p-i-n quantum well waveguide photodiodes, and its application to fiber Bragg grating strain sensor have been demonstrated. Ridge waveguide photodiodes with five different quantum well structures have been de signed, fabricated and characterized. In a wavelength monitoring system that employed a single-segment photodiode, the waveguide photodiode was used as either a tunable edge filter or a wavelength selective photodetector. A wavelength resolution of 1 pm with an operating range of 18 nm was achieved with a GaAs/AlGaAs multiple quantum well device. In a wavelength monitoring system that employed a pair of in-line waveguide photodiodes, the photocurrent ratio of the two photodiodes varied linearly with wavelength in a region near the absorption band edge. A wave-length resolution of 0.4 pm was achieved with InGaAs/GaAs quantum well devices for TE-polarized light with intensities of about 30 μW and a signal averaging time of 0.2 seconds. An operating range of 40 nm was obtained by voltage tuning of the quantum wells. The photocurrent ratios in the in-line waveguide photodiodes were also used to determine the absorption coefficients of the photodiodes. The shifts of the exciton peak positions with the applied bias voltage showed fairly good agreements with the predictions of a variational theory. The photocurrent ratio of the in-line quantum well waveguide photodiodes showed strong polarization dependence. However, the separation between the absorption edges for the TE and TM polarizations was so large that this device could be used in the wavelength range near the absorption edge of the TE component even in the presence of a large TM component in the input. An optical fiber Bragg strain sensing system, that consists of a superluminescent diode, a 2 x 2 fiber coupler, a fiber Bragg grating and the waveguide detector, was assembled to demonstrate the application of the developed wavelength monitor. A strain resolution of 5 microstrain has been obtained with the fiber Bragg grating strain sensor. The grating strain sensor shows a linear response over a range of ±2500 microstrain.
Keywords: Engineering Physics; Engineering Physics